Epidemiological Impact and Cost-Effectiveness of Varicella Vaccination Strategies in the United Kingdom. (11th November 2020) - Akpo, Esse Ifebi Herve; Cristeau, Olivier; Hunjan, Manjit; Casabona, Giacomo
Abstract: Background: Despite the burden of varicella, there is no universal varicella vaccination (UVV) program in the United Kingdom (UK) due to concerns that it could increase herpes zoster (HZ) incidence. We assessed the cost-utility of a first-dose monovalent (varicella [V]) or quadrivalent (measles-mumps-rubella-varicella [MMRV]) followed by a second-dose MMRV UVV program. GSK and MSD varicella-containing vaccines (VCVs) were considered. Methods: Dynamic transmission and cost-effectiveness models were adapted to the UK. Outcomes measured included varicella and HZ incidences and the incremental cost-utility ratio (ICURs) over a lifetime horizon. Payer and societal perspectives were evaluated. Results: The impact of V-MMRV and MMRV-MMRV UVV programs on varicella incidence was comparable between both VCVs at equilibrium. HZ incidence increased by 1.6%–1.7% over 7 years after UVV start, regardless of the strategies, then decreased by >95% at equilibrium. ICURs ranged from £5665 (100 years) to £18 513 (20 years) per quality-adjusted life-year (QALY) gained with V-MMRV and from £9220 to £27 101 per QALY gained with MMRV-MMRV (payer perspective). MMRV-MMRV was cost-effective in the medium- and long-terms with GSK VCV and only cost-effective in the long term with MSD VCV at a £20 000 per QALY gained threshold. Without the exogenous boosting hypothesis, HZ incidence decreased through UVV implementation. ICURs were most sensitive to discount rates and MMRV price. Conclusions: A 2-dose UVV was demonstrated to be a cost-effective alternative to no vaccination. With comparable effectiveness as MSD VCV at lower costs, GSK VCV may offer higher value for the money. Abstract : A 2-dose universal varicella vaccination was demonstrated to be a cost-effective alternative to no vaccination. With comparable effectiveness as MSD varicella-containing vaccines (VCVs) at lower costs, GSK VCV may offer higher value for the money.